Is socially responsible investing really beneficial? New empirical evidence for the US and European stock markets - Janick Christian Mollet; Andreas Ziegler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper empirically examines the theoretically ambivalent relationship between socially responsible investing (SRI) and stock performance. It extends the existing literature by considering both the US and the entire European stock markets as well as by using consistent world-wide corporate sustainability performance data. Our portfolio analysis from 1998 to 2009 reveals the appeal of a recently constructed financial databank comprising the common market return, size, value, and momentum factors according to Carhart (1997). These risk factors from the four-factor model allow us to estimate more reliable risk-adjusted returns than in the restrictive one-factor model based on the Capital Asset Pricing Model. In both the US and European stock markets we find that SRI is associated with large-sized firms. However, this investment strategy generally leads to insignificant abnormal returns when all four risk factors are considered so that we find no evidence that SRI is either penalized or rewarded by the stock markets.
Keywords: G11; G12; Q56; M14; 330; Socially responsible investing; Corporate sustainability performance; Stock performance; Portfolio analysis; Asset pricing models; Risk factors; Ethische Geldanlage; Umweltmanagement; Corporate Social Responsibility; Börsenkurs; Rendite; Risiko; Schätzung; USA; Europa